The Concept Of Matan Critism And Its Application In The Book Al-Tamyīz By Muslim Bin Ḥajjāj - Dzulfaidhi Hakimie Dzulraidi (Rabbanica: Journal of Revealed Knowledge)
The criticism of matn (text) is a process of determining the status of a hadith by identifying flaws within its text. This process is widely used in hadith studies, particularly in the science of ‘ilal al-hadith. However, there is still a lack of research that systematically highlights the practices of hadith scholars in this field. Among the renowned hadith scholars in ‘ilal al-hadith is Muslim bin al-Hajjāj. The recognition from many other hadith scholars evidences this. Furthermore, tangible proof can be observed in his work, al-Tamyīz, within this branch of knowledge. Therefore, this article aims to dissect the concept and practical application of matn criticism by Muslim bin al-Hajjaj, based on his work al-Tamyīz. The study employs the documentation method, with al-Tamyīz as the primary reference, alongside classical and contemporary works and academic articles for data collection. A content analysis method analyses the collected materials to achieve comprehensive results. The study found that Muslim bin al-Hajjaj applied matn criticism in 17 instances to resolve all issues of ‘illah. However, the forms of matn criticism varied depending on the specific hadith issues. Moreover, the analysis revealed that he employed several interesting types of qarīnah (indicators) in matn criticism that merit further detailed discussion, such as narrative storytelling, textual anomalies, and contradictions with historical facts. Thus, the study recommends further research on these topics to enrich the field of hadith studies in Malaysia.